Irreducible components of extended eigenvarieties and interpolating Langlands functoriality - Johansson, C; Newton, J (International Press, 2019)
We study the basic geometry of a class of analytic adic spaces that arise in the study of the extended (or adic) eigenvarieties constructed by Andreatta–Iovita–Pilloni, Gulotta and the authors. We apply this to prove a general interpolation theorem for Langlands functoriality, which works for extended eigenvarieties and improves upon existing results in characteristic 0. As an application, we show that the characteristic p locus of the extended eigenvariety for GL2/F, where F/Q is a cyclic extension, contains non-ordinary components of dimension at least [F : Q] .